Striking the Right Note : Key Performance Indicators for Sovereign Sustainability-Linked Bonds - Flugge, Mark L.; Mok, Rachel C.K.; Stewart, Fiona E. (World Bank, Washington, DC, 2022)
The framework presented in the report is intended to bridge the gap between what sovereign investors will view as appropriately ambitious actions and what issuing countries see as achievable targets. The framework is intended to help investors with their decision-making and can inform Ministries of Finance and their debt management offices (DMOs) about what investors want to know regarding their country’s sustainability performance. The report findings may also inform creation of financial instruments and market analyses beyond sovereign sustainability-linked bonds (SLBs) and are relevant for a broad range of stakeholders. These include regulators, credit rating agencies, academics, as well as nongovernmental organizations (NGOs), and civil society groups which can be affected by the types of indicators selected and outcomes of government policies.